Political struggle in cyberspace (Twitter) in times of COVID-19 (Peru: march – may – august 2020) - Aliaga Lodtmann, Cluber Fernando (2020)
This research has allowed us to know the most important characteristics of the political struggle being waged in Peru by the political parties that are represented in the Congress of the Republic and the National Government represented by the President of the Republic and the ministries that have been the main agents in the fight against Covid-19.  The study period covers since March 1, 2020, being the month in which the State of Sanitary Emergency began in Peru, with the quarantine and social isolation established by the national government to halt the increase of Covid-19, until August 31, 2020, when Peru became the first country in the world in the mortality rate caused by Covid-19 (Gestion Newspaper, 2020).  During the period under study, the Congress of the Republic has denied the vote of confidence to the Ministerial Cabinet chaired by Pedro Alvaro Cateriano Bellido in the early morning of August 4, 2020 [Congreso Noticias (News Congress), 2020] and the enactment of regulations by the Congress of the Republic that were considered unconstitutional by the National Government, such as the Law for the suspension of toll collection, for which the Executive Branch filed a complaint of unconstitutionality (Gestion Newspaper, 2020).  A thorough review of current theory and previous research related to the topic was carried out. The conclusions allow us to point out that the political struggle in the cyberspace social network twitter has been irregular, differentiated and dissimulated, avoiding direct conflict, without observing defined strategies, preferring populist messages and where few parties show themselves to be moderately opposed to the national government.